Reproductive problems in indigenous cattle in the Ghibe valley farming populations in central Ethiopia - Tekelye Bekele; Kasali, O.B.; Wudyalew Mulatu (1992)
Determines the reproductive performance and problems in indigenous cattle at the Ghibe valley farming populations in central Ethiopia. Discusses the constraints of reproductive performance in cattle, such as genital infections, nutrition, traditional management, prenatal losses like embryonic mortality and abortion. Suggests the control of the seasonal flare up of trypanosomiasis and other health-management interventions as the possible remedy to overcome reproductive wastage in the future.